Exploring the Challenges Faced by Single Mothers in Guyana - Kumar, Suraj (Journal of Social Science and Humanities, 2024)
A single mother is one who lives alone with her children and leads a life without her partner due to death, separation, or divorce. This situation of being a single woman can change the personality and behavior, which can be from within the person's inner sense or from society. This study aspires to show the hustles, tussles, and wrestles of single mothers in Guyana; the challenges, the reason to become a single mother, the management of financial matters, and the stress they go through. The intention of the study is to learn the challenges they face in caring for their children and the struggles in making decisions to run the family. This study also focuses on the personal, emotional, social, and financial challenges in a single mother’s life. The objective of the study is the deep pursuit of knowledge for academic achievements and my personal interest in learning about single mothers’ life. Samples of 57 single mothers were selected by purposive sampling technique. The researcher selected the participants from different Regions of the country. The researcher made an open dialogue with the participants using an exploratory method. The second type of sampling was collected by fourteen prepared multiple - choice questions. Most of the participants reported that they had regular fights in the family and were cheated by their partners and an unhealthy family environment was created which led to separation followed by financial difficulties and stress.61% of the participants haven’t built and maintained a support network as single mothers. 80.77% of single mothers ignore their children’s questions regarding their father and their behavior issues. The findings of the study aim to benefit future researchers who can use this study to contribute to the single - parenthood struggles in society. The results suggest that single mothers should seek financial and professional help from competent and trained counselors.